The evaluation of the possibility of the estimation the amount of hemagglutininin in the final lots of inactivated adjuvanted influenza vaccines - Aleksey Y. Butirskiy; Elena N. Morozova; Karine A. Sarkisyan (Вопросы вирусологии)
Introduction. The main quality indicator for inactivated influenza vaccines is their potency (the amount of hemagglutinin). The potency test for the influenza vaccine with the SOVIDON adjuvant is carried out in a trivalent bulk vaccine before the addition of the adjuvant. This approach has its fair share of drawbacks. The analysis of the statistical process control and stability by control charts plays an important role in the release of influenza vaccines.